Narrative strategies of the Romantic “philosophical epics” in the piano works of Franz Liszt (Analysis o/Sposalizio, Valee D’Obermann, Ballade No. 2 and the Sonata in B minor) - Grabocz, Marta (Interdisciplinary Studies in Musicology, 2018)
The article explains how ideas, characters and images borrowed from literary works and of fine arts are represented in Liszt’s the piano works of (i.e. with the help of motives, themes and narrative strategies). I. The first level of analysis concerns the typology of basic elements in the new lisztian forms: A. Four types of musical motives or figures and their signifieds (semes). B. Sixteen types of musical themes with their signifieds (classemes). C. Considering the great parts or sections of a piece we discovered seven types with their signifieds (isotopies). II. The second level of analysis consists in the presentation of three types of narrative strategies. The narrative strategy would mean the conscious organization of concatenation of the above mentioned signifying elements. A. The “figurative strategy” refers to the formal variation [‘Formalvariation” in German] of onetheme, or of one “thematic complex” (theme introduced and followed by expressive describing motives or refrain), for example: Sposalizio. B. The “simple narrative strategy” consists in a succession of character variations [‘Charaktervariation’], i.e. variation in the musical genre, in the signified of one musical theme (for example: Vallee d’Obermanri). C. The “complex narrative strategy” describes the structures which combine sonata form, cyclical sonata in four movements and variation form. This strategy implies that a whole thematic complex (exposition) is submitted to different stages of the character variation (for example: Dante sonata, Sonata in B minor, 2nd Ballade in B minor, etc.).